FAKTOR-FAKTOR PENENTU PROFITABILITAS : STUDI RECEIVABLE TURNOVER DAN DEBT TO ASSET RATIO DI SEKTOR PERTANIAN BEI - Munika, Rani; Rahmawati, Rahmawati; Helmiati, Helmiati (Jurnal Akuntansi Kompetif, 2024)
Study aims to analyze the effect of This and Ratio to Return On Assets. The population in this study were 26 agricultural sector companies listed on the Indonesia Stock Exchange for the period 2018-2021. The sampling technique used is purposive sampling and obtained a sample of 15 companies. The data used is secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange website (www.idx.co.id). The analysis technique used in this research is multiple linear regression. The results showed that Receivable Turnover had no effect on Return On Assets while the Debt to Asset Ratio had a significant effect on Return On Assets. The close relationship that occurs between the Receivable Turnover and Debt to Asset Ratio is categorized as moderate with a correlation coefficient of 44.7% and the contribution of the independent variable to the dependent variable is 20% while 80% is influenced by other variables not included in this research model. Keywords: Receivable Turnover, Debt to Asset Ratio, Return On Assets.